Description of the direct teaching activities of itinerant teachers of deaf and hard of hearing students. (2nd January 2018) - Davison-Mowle, John; Leigh, Greg; Duncan, Jill; Arthur-Kelly, Michael
ABSTRACT: This study sought to describe and classify the support activities provided by all itinerant teachers for students who are deaf or hard of hearing (DHH) in regular schools in the Australian Capital Territory (ACT), without exclusion. The itinerant teachers ( n  = 14) varied in terms of formal qualifications and experience and provided support to all DHH ( n  = 61) students in ACT schools, inclusive of students across all age/grade levels and those with additional disabilities. Analysis of teachers' responses to a detailed questionnaire provided frequency and time measures for 22 possible activities, which were simplified using factor analysis into 11 categories of activities. Categorization of the activities indicated that 91% of the support time was used for direct teaching, and that 73% of the direct teaching time was primarily focused on the development of skills in language, listening, and speech. The other 27% of the direct teaching time was used for explicit class programme support. As well as providing direct teaching, the itinerant teachers provided consultation services to school personnel and parents. The findings are discussed in relation to the previous literature describing the activities of itinerant teachers of DHH students.